Architectures of enmity in Andre Dubus III’s The Garden of Last Days - M. Ikbal M. Alosman; Raihanah M. M.; Ruzy Suliza Hashim (Penerbit Universiti Kebangsaan Malaysia, 2018)
In the aftermath of 9/11 terrorist attacks, Islam and Muslims became the subject of representation in the American literary milieu. American novelist Andre Dubus III was one of those who have appropriated the attacks directly by characterizing 9/11 hijackers within his bestseller novel, The Garden of Last Days (2009). This paper sets out to investigate Andre Dubus’ III demonstration of Islam and Muslims in line with their association with terrorism and intolerance towards non-Muslims. We also seek to contextualize Dubus’ exemplification of the Muslim Other within pertaining geopolitical and Orientalist inferences. As post-9/11 literature has been highly immersed in the cultural, colonial and political ramifications of the attacks, both postcolonial and geopolitical concepts are incorporated into a geopolitical postcolonial approach. Geopolitical postcolonial approach is meant to illustrate the narrative’s exemplification of Islam and Muslim in view of the geopolitical consequences of 9/11 attacks as well as the long established Western knowledge about the Orient, Orientalism. Architectures of enmity are the deliberated schemes exploited to shape the other into a differentiated and abhorred adversary to initiate violence against him/her. Dubus’ architectures of enmity will be examined within four constructs, specifically, ‘hatred,’ ‘Islamic agency,’ ‘clashing Islam’ and ‘Arabic antagonism.’ In The Garden of Last Days, the Muslim Other is exemplified as the enemy of the West. Islam is illustrated as an antagonist ideology that leads Muslims to hate all non-Muslims. Through the geopolitical postcolonial lens we expose the circumstantial implications of these representations and relate them to their due context.